2022
DOI: 10.3389/fimmu.2021.785091
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint LAG3 and Its Ligand FGL1 in Cancer

Abstract: LAG3 is the most promising immune checkpoint next to PD-1 and CTLA-4. High LAG3 and FGL1 expression boosts tumor growth by inhibiting the immune microenvironment. This review comprises four sections presenting the structure/expression, interaction, biological effects, and clinical application of LAG3/FGL1. D1 and D2 of LAG3 and FD of FGL1 are the LAG3-FGL1 interaction domains. LAG3 accumulates on the surface of lymphocytes in various tumors, but is also found in the cytoplasm in non-small cell lung cancer (NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 99 publications
3
90
0
1
Order By: Relevance
“…Further studies reproduced the anti-tumor effect of TIGIT using human PBMCs [96,97]. These findings of efficacy of targeting other co-inhibitory molecules led to clinical trials of LAG-3 [98], TIM-3 [99], and TIGIT [100] in patients with cancer. In summary, many studies and trials have been conducted using ICIs to treat cancer.…”
Section: Characteristicsmentioning
confidence: 81%
“…Further studies reproduced the anti-tumor effect of TIGIT using human PBMCs [96,97]. These findings of efficacy of targeting other co-inhibitory molecules led to clinical trials of LAG-3 [98], TIM-3 [99], and TIGIT [100] in patients with cancer. In summary, many studies and trials have been conducted using ICIs to treat cancer.…”
Section: Characteristicsmentioning
confidence: 81%
“…However, it was reported that LAG3 expression was associated with an improved overall survival (OS) compared to patients without LAG3 expression in oesophageal adenocarcinoma ( 27 ). LAG3 may serve as a biomarker for a strong immune response, and the two opposite immune functions (positively or negatively) of LAG3 can be attributed to the complexity of tumor immune microenvironment and tumor heterogeneity ( 28 ). The function of LAG3 in melanoma needs further experiments to verify.…”
Section: Resultsmentioning
confidence: 99%
“…This contradictory pattern has also been observed in breast cancer. In ER - and ER + breast cancer, high expression of LAG-3 predicted a favorable outcome ( 109 , 110 ). However, dual-positive LAG-3 and PD-1 were correlated with an unfavorable prognosis in terms of decreased DFS ( 111 ).…”
Section: Preclinical Data In Esophageal Cancermentioning
confidence: 99%